Sprowadz do najprostrzej wersji . (czy jakos tam xd) .
Np .
4ab - 5a + 6 - 2ab +5a -4 =
-4ab - 2ab -5a + 5a +6-4=
-6ab+2.

a) ( 2xy-4x+3)+(-2xy + 4x -3)=
b) (-5x ( do potegi 2 ) +2xy (do potegi 2 ) -3x )+(2xy(do potegi 2 ) -3xy(do potegi drugiej + 2y )=
c) (-4ab ( do potegi 2 ) - 3ab + 4a - 5 )+( 3ab ( do potegi 2 )+ 3ab -7a-3)=

2

Odpowiedzi

2010-01-09T20:29:31+01:00
A) ( 2xy-4x+3)+(-2xy + 4x -3)=
2xy-4x+3 - 2xy +4x - 3=
=0

b) (-5x² +2xy² -3x )+(2xy² -3xy² + 2y )=
=-5x²+xy² -3x+ 2y

c) (-4ab² - 3ab + 4a - 5 )+( 3ab²+ 3ab -7a-3)=
= -ab² -3a -8
1 4 1
2010-01-09T20:34:11+01:00
A)( 2xy-4x+3)+(-2xy + 4x -3)=2xy-4x+3-2xy+4x-3=3
b) (-5x ( do potegi 2 ) +2xy (do potegi 2 ) -3x )+(2xy(do potegi 2 ) -3xy(do potegi drugiej + 2y )= nie moge tego rozczytac
c) (-4ab ( do potegi 2 ) - 3ab + 4a - 5 )+( 3ab ( do potegi 2 )+ 3ab -7a-3)=-4ab ( do potegi 2 ) - 3ab + 4a - 5 +3ab ( do potegi 2 )+ 3ab-7a-3=-8-1ab( do potegi 2 ) - 3a